Enhancing Arabic Translation Competency In Higher Education: An Evaluation Of The Becoming A Translation Practitioner' Program/ تعزيز مهارات الترجمة للغة العربية في التعليم العالي: تقييم برنامج أن تصبح ممارسًا للترجمة - Baihaqi, M; Syarifah, Ainun; Arif, Muthahir (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to evaluate the effectiveness of the